2015
DOI: 10.1155/2015/365845
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms rs12998 and rs5780218 inKiSS1Suppressor Metastasis Gene in Mexican Patients with Breast Cancer

Abstract: Aims. KiSS1 is a metastasis suppressor gene associated with inhibition of cellular chemotaxis and invasion attenuating the metastasis in melanoma and breast cancer cell lines. Along the KiSS-1 gene at least 294 SNPs have been described; however the association of these polymorphisms as genetic markers for metastasis in breast cancer studies has not been investigated. Here we describe two simple PCR-RFLPs protocols to identify the rs5780218 (9DelT) and the rs12998 (E20K) KiSS1 polymorphisms and the allelic, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…One SNP we examined, rs3795573, was predicted to affect binding (RegulomeDB score 2b). One prior study found that rs5780218 was significantly associated with risk of breast cancer among Mexican patients , but this SNP is not in LD with any of the ones we included.…”
Section: Discussionmentioning
confidence: 76%
“…One SNP we examined, rs3795573, was predicted to affect binding (RegulomeDB score 2b). One prior study found that rs5780218 was significantly associated with risk of breast cancer among Mexican patients , but this SNP is not in LD with any of the ones we included.…”
Section: Discussionmentioning
confidence: 76%
“…KiSS-1 is considered a metastatic suppressor in many cancers [ 11 , 25 , 26 ]. Results have demonstrated that the normal expression of KiSS-1 can suppress tumor cell growth, motility, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…The KiSS-1 gene, which encodes a 145-amino-acid protein, can bind to the G protein-coupled receptor 54 (GPR54, also called KiSS-1R). KiSS-1 can control cell-cell adhesion by promoting E-cadherin expression and cell-matrix adhesion and cytoskeleton remodeling through inhibition of MMP expression [ 11 , 24 , 25 ]. KiSS-1 expression is also reported to suppress the metastatic potential of tumor cells but not tumorigenicity [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations